Traction control–integrated energy management strategy for all-wheel-drive plug-in hybrid electric vehicle - Dafeng Song (Advances in Mechanical Engineering, 2017)
Plug-in hybrid electric vehicle is one of the potential candidates to tackle the stringent fuel economy standards. Many previous studies focus on optimal fuel economy by coordinating primary power source and assistant power source in plug-in hybrid electric vehicles, which usually neglects vehicle dynamic performance. All-wheel-drive plug-in hybrid electric vehicle has advantages both in fuel economy and dynamic performance. However, when all-wheel-drive plug-in hybrid electric vehicle is traveling on low cohesive roads, how to balance the conflict between traction performance and fuel economy undoubtedly will be the crucial problem. To address the issue, an integrated control strategy is proposed for all-wheel-drive plug-in hybrid electric vehicle in this article, namely, traction control system–integrated energy management strategy. A charge depletion/charge sustaining strategy is employed to realize the torque distribution mainly according to the engine optimal working region to achieve better fuel economy. Traction control system is integrated to prevent slipping of the wheels during starting and acceleration by applying engine throttle control, motor torque control, and active braking control, which improves the vehicle dynamic performance. The traction enhancement is beneficial to the improvement of fuel efficiency. By the co-simulation of MATLAB/Simulink and AMESim, the results demonstrate the effectiveness of the proposed integrated control strategy, which increases the vehicle velocity greatly and optimizes fuel economy as well.